The manufacturing and soft robotic applications of free stroke twisted and coiled actuators - Tighe, Brandon Z., author; Zhao, Jianguo, advisor; Endeshaw, Haile, committee member; Simske, Steve, committee member (Colorado State University. Libraries, 2022)
Inspired by biological systems (e.g., octopus), soft robots made from soft materials outperform traditional rigid robots in terms of safety and adaptivity because of their compliant and deformable bodies. To enable a soft robot's unique capabilities, they require a key component—the actuator. Many different actuators have been used, including the conventional pneumatic-driven and cable driven methods, and also several emerging approaches, like dielectric elastomers, liquid crystal elastomers, and shape memory alloys. Besides existing actuation approaches, another promising actuator for soft robots is the twisted-and-coiled actuator (TCA), which can be conveniently fabricated by continuously twisting polymer fibers into a coiled spring-like shape. In this thesis, we investigate free stroke TCAs (i.e., TCAs that can produce significant displacements without preloading). We first describe a customized machine that can automatically fabricate TCAs with free strokes by twisting a polymer fiber and then coiling the twisted fiber along a mandrel with a guide channel, which is made by wrapping a small copper wire helically about a larger one. After that, we discuss the characterization and evaluation of the fabricated TCAs. We also apply free stroke TCAs to two different soft robotic systems. The first one is a spherical tensegrity robot which resembles a tensegrity structure, a compliant yet stable structure made of rigid rods and elastic cables. By replacing the elastic cables with TCAs, we can actuate TCAs to shift the robot's center of gravity to generate rolling locomotion. The second application is a shape morphing quadrupedal robot with multiple modes of locomotion. By actively morphing the robot's body shape, we demonstrate different locomotion modes for the same robot, including walking on flat ground, crawling below a gap, and climbing across a bridge. Demonstrations for the tensegrity robot and shape morphing robot will facilitate future biologically inspired adaptive robotic systems to actively adapt their morphologies and behaviors to different environments.